Ovarian Cancer Population Screening and Mortality After Long-Term Follow-up in the UK Collaborative Trial of Ovarian Cancer Screening (UKCTOCS): A Randomised Controlled Trial. Issue 9 (September 2021) - Menon, Usha; Gentry-Maharaj, Aleksandra; Burnell, Matthew; Singh, Naveena; Ryan, Andy; Karpinskyj, Chloe; Carlino, Giulia; Taylor, Julie; Massingham, Susan K.; Raikou, Maria; Kalsi, Jatinderpal K.; Woolas, Robert; et al.
Abstract : (Abstracted from Lancet 2021;397:2182–2193) Ovarian cancer is most commonly diagnosed at an advanced stage (3 or 4) and remains the deadliest gynecologic malignancy. When diagnosed at stage 1, a survival rate of greater than 90% has been demonstrated, compared with a 5-year survival rate of 27% and 13% for stage 3 and stage 4 disease, respectively.